Evaluation of the psychometric properties of a modified version of the Social Phobia Screening Questionnaire for use in adolescents - Svedin Carl; Furmark Tomas; Tillfors Maria; Björklind Andreas; Gren-Landell Malin; Andersson Gerhard (BMC, 2009)
Abstract Background Social phobia (social anxiety disorder - SAD) is a rather common but often undetected and undertreated psychiatric condition in youths. Screening of SAD in young individuals in community samples is thus important in preventing negative outcomes. The present study is the first report on the psychometric properties of the Social Phobia Screening Questionnaire for Children and adolescents (SPSQ-C). Methods The SPSQ-C was administered to a community sample of high-school students. Test-retest reliability over three weeks was evaluated (n = 127) and internal consistency was calculated for items measuring level of fear in eight social situations. To measure concurrent validity, subjects who reported SAD on at least one occasion and randomly selected non-cases were blindly interviewed with the Structured Clinical Interview for DSM-IV Axis-I disorders (SCID-I), as gold standard (n = 51). Results A moderate test-retest reliability, r = .60 (P < .01), and a satisfactory alpha coefficient of .78 was found. Values of sensitivity and specificity were 71% and 86% respectively, and area under the curve (AUC) was .79. Positive likelihood ratio (LR+) showed that a positive screening result was five times more likely to be correct than to reflect a non-case. Negative likelihood ratio (LR -) was .34. In addition, positive predictive value was 45% and negative predictive value was 95%. The prevalence of self-reported SAD was found to be 7.2% at the first assessment. Conclusion The SPSQ-C is a short and psychometrically sound questionnaire for screening of SAD in adolescents, with the advantage of being based on the DSM-IV criteria.